In-service ELT Teachers’ Perception on Learning Management System (LMS) Implementation during Teacher Educational Education Program (PPG) - Rahmiyatus Shalihah; Syafryadin Syafryadin (Edu-Ling: Journal of English Education and Linguistics, 2023)
Abstract LMS as learning management software has increasingly utilized to perform online classes mostly in tertiary level of education. Therefore, study is aimed to evaluate how in-service ELT teachers’ perception toward Learning Management System (LMS) in online learning during their Teacher Professional Education Study Program (PPG). The total population of 26 in-service teachers was taken as the subject of the research. The methodology used in the study was descriptive quantitative which specified into survey research. The data finding of the study was gotten from 14 items questionnaire and one open-ended question, which were counted using mean value and percentage. From the study it was discovered that in-service PPG students had very good perception on the LMS implementation in online learning. The finding also revealed that the ICT integration in online learning was well-received. Keywords: ICT, Learning Management System, and online learning.